Palavra e imagem: signos do presidente Lula na mídia impressa. - Formentão, Francismar (2008)
This research aims at the semiotic study of the discursive headings about President Luiz Inacio Lula da Silva, present on the covers of the newspapers Folha de S.Paulo and O Estado de S. Paulo in May and June of 2006. With Mikhail Bakhtin, is based the theorical and methodological field of this research through the analysis and interpretation of relationships embodied in signs in the society. Bakhtin, through the philosophy of language, specifies that the language is a material product from the ideological creation, and the signs universe is the universe of ideology, with mutual correspondence , reflecting and refracting the material reality of society. The ideological sign in Bakhtin s understanding , allows to demonstrate how word and image are articulated composing ideological spheres and social fields, seen in this research of newspaper covers. It is articulated the elements that compose visually the communication vehicle of journalism, with the correspondence of sign materiality in dialogism of communication. The various categories / concepts of Bakhtin compose a conceptual architectural that in a semiotic - dialectical axis allows to analyze the journalistic information existing in newspapers. This research demonstrates the alterity process of the sign evidenced in the reflexive synthesis the senses materialized in journalism communication, present on the covers of newspapers and in the imagined institutions of society by presenting objective refractions of the senses.